Who leaps first: Status quo of the leapfrogging phenomenon - Jan F. Killmer (Managerial and Decision Economics, 2023)
In an economic environment, the leapfrogging phenomenon manifests itself in various facets and makes it possible to skip stages of development or product generations. However, an overview of the actors that are involved, how they are connected, and the effects that leapfrogging can have is missing. This article thus focuses on identifying relevant research contributions and analyzing their content by text mining. The results reveal that various actors engage in leapfrogging and that this phenomenon plays a major role in the development of countries, for instance. Firms and industries also pursue leapfrogging, for example, to take leading positions in the market (business strategies). An area of research that has received little attention thus far addresses the leapfrogging behavior of consumers. Technological leapfrogging also combines numerous elements of this phenomenon. Therefore, this article derives many relevant topics for research and practice to investigate this phenomenon in a more accurate and targeted manner.
Keywords: 650